VD_FINDINFO AI 43/14 - 79/2016 vom 16. März 2016 - VD Tribunal cantonal (2016)
INCAPACITÉ DE TRAVAIL, RENTE D'INVALIDITÉ, MÉTHODE MIXTE D'ÉVALUATION | 28 LAI, 28a LAI, 4 LAI, 16 LPGA, 7 LPGA, 8 LPGA, 27 RAI